(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The use of the ecotourism potential of protected natural areas for the purpose of organizing ecotourism has been a global trend for many years. The article describes the key aspects of the development of ecological tourism in protected natural areas.